Психологія ціноутворення та сприйняття вартості у B2B - Makhmudova, Anna (Академічні візії, 2024)
The article explores the psychological aspects of pricing and value perception in B2B communication. The aim of the study is to identify the key psychological mechanisms that influence how a commercial offer is perceived in the B2B context, and to justify effective pricing strategies that can enhance price elasticity and the competitiveness of business products. The research employed general scientific methods of cognition: analysis, synthesis, induction, deduction, comparison, modeling, the systems approach, and generalization. The findings show that value perception in the B2B environment is shaped not only by rational factors such as cost analysis or ROI, but is also heavily influenced by psychological triggers. These include reference pricing, perceived value, anchoring, scarcity, social proof, and the symbolic interpretation of price as an indicator of quality or status. It is demonstrated that a commercial offer designed with these psychological mechanisms in mind transforms price from a neutral numerical figure into a strategic element of marketing communication, increasing the likelihood of a positive response from potential clients, even in cases of high pricing. The study reveals that successful negotiation strategies in today’s B2B sphere are largely driven by psychological triggers that reshape how value is perceived. It concludes that such triggers not only help justify high pricing but also serve as tools for enhancing brand prestige, differentiating the commercial offer, and building client trust. The use of scarcity, urgency, social proof, authority, reciprocity, likability, uniqueness, and value principles within the structure of a commercial proposal makes it possible not only to justify premium pricing but also to reframe it – from a cost to an investment in meaningful value. This, in turn, boosts price elasticity and strengthens the brand’s market position within the high-value segment. The practical value of the study lies in its potential to inform the development of effective B2B pricing strategies based on psychological drivers of influence.